Evaluation of lung homogeneity in neonates and small infants during general anaesthesia using electrical impedance tomography: a prospective observational study - Vanessa Marchesini; Sebastian Corlette; Suzette Sheppard; Andrew Davidson; David Tingay (BJA Open)
Background: Prolonged mechanical ventilation can create heterogeneous ventilation patterns, which increase the risk of lung injury in infants. However, little is understood about the risk of brief exposure to mechanical ventilation during anaesthesia. The aim of this prospective observational study was to describe the regional pattern of lung ventilation during general anaesthesia in healthy neonates and infants, using electrical impedance tomography. Methods: Twenty infants (age 3 days to 12 months), without known lung disease and receiving general anaesthesia with endotracheal intubation for supine positioned surgery, were included in the study. Anaesthesia and ventilation management was at the discretion of the treating clinician. Standardised lung imaging using electrical impedance tomography was made at six time points during anaesthesia from induction to post-extubation. At each time point, the gravity-dependent and right–left lung centre of ventilation was calculated. Results: Tidal ventilation favoured the dorsal lung regions at induction, with a median (inter-quartile range) centre of ventilation (CoV) of 58.2 (53.9–59.3)%. After intubation, there was a redistribution of ventilation to the ventral lung, with the greatest change occurring early in surgery: CoV of 53.8 (52.3–55.2)%. After extubation, CoV returned to pre-intubation values: 56.5 (54.7–58)%. Across all time points, the pattern of ventilation favoured the right lung. Conclusions: General anaesthesia creates heterogenous patterns of ventilation similar to those reported during prolonged mechanical ventilation. This potentially poses a risk for lung injury that may not be recognised clinically. These results suggest the need to better understand the impact of general anaesthesia on the developing lung. Clinical trial registration: Australian New Zealand Clinical Trials Registry (ACTRN 12616000818437, 22 June 2016).